2017
DOI: 10.1093/eurheartj/ehx011
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones affect outcome in arrhythmogenic right ventricular cardiomyopathy/dysplasia: from a stem cell derived cardiomyocyte-based model to clinical biomarkers of disease outcome

Abstract: Aims Arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) is characterized by fibrofatty infiltration of the myocardium and ventricular arrhythmias that may lead to sudden cardiac death. It has been observed that male patients develop the disease earlier and present with more severe phenotypes as compared to females. Thus, we hypothesized that serum levels of sex hormones may contribute to major arrhythmic cardiovascular events (MACE) in patients with ARVC/D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 42 publications
9
102
0
Order By: Relevance
“…19 In patients with arrhythmogenic cardiomyopathy estradiol appears to have a protective and testosterone a detrimental effect across both sexes. 20 Increased levels of estradiol reduced myocyte apoptosis in an in vitro model of arrhythmogenic cardiomyopathy, while increased testosterone levels potentiated it. Myocyte death is central to the development of replacement fibrosis and it is possible that the different impact of these sex hormones on myocyte survival contributes to a higher prevalence of replacement fibrosis in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In patients with arrhythmogenic cardiomyopathy estradiol appears to have a protective and testosterone a detrimental effect across both sexes. 20 Increased levels of estradiol reduced myocyte apoptosis in an in vitro model of arrhythmogenic cardiomyopathy, while increased testosterone levels potentiated it. Myocyte death is central to the development of replacement fibrosis and it is possible that the different impact of these sex hormones on myocyte survival contributes to a higher prevalence of replacement fibrosis in men.…”
Section: Discussionmentioning
confidence: 99%
“…Protection from cardiovascular disease in pre‐menopausal women has been linked with sex hormones, including estradiol . In patients with arrhythmogenic cardiomyopathy estradiol appears to have a protective and testosterone a detrimental effect across both sexes . Increased levels of estradiol reduced myocyte apoptosis in an in vitro model of arrhythmogenic cardiomyopathy, while increased testosterone levels potentiated it.…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic causes of AC are less well studied, but data suggest that for mutations in TMEM43 , RBM20 , the founder R14del in phospholamban and FLNC , sudden death risk relates to the severity of structural and functional abnormalities, although anecdotal reports and familial evaluation suggest that sudden death can be the initial presenting feature . Several novel disease biomarkers that might aid risk prediction are under study, such as testosterone, BIN‐1, soluble ST2 and anti‐desmoglein‐2 autoantibodies . However, these have not been compared with conventional risk factors.…”
Section: How Can Sudden Cardiac Death Prediction Be Improved In Arrhymentioning
confidence: 99%
“…16,30 Several novel disease biomarkers that might aid risk prediction are under study, such as testosterone, BIN-1, soluble ST2 and anti-desmoglein-2 autoantibodies. 64 may provide a means for reducing arrhythmic risk but require sensitive and specific biomarkers of disease activity and therapeutic response.…”
Section: How Can Sudden Cardiac Death Prediction Be Improved In Arrhymentioning
confidence: 99%
“…A number of studies have reported that carriers of multiple mutations in the same desmosomal gene, or mutations in two or more genes are at higher arrhythmic risk than those with a single mutation 6,55 . It is noteworthy that in a multivariable model analysis, multiple desmosomal gene mutations and male gender resulted independent predictors of life-time major arrhythmic events with a Hazard Ratio (HR) of 2.3 and 2.9, respectively 55 .…”
Section: Selected Topics In Risk Stratification Of Arvc Patientsmentioning
confidence: 99%